Wine tourism experience effects on co-creation, perceived value and consumer behavior - Zhang Yuqing; Lee Hoffer (Ciência e Técnica Vitivinícola, 2022)
Wine tourism is an increasingly prevalent form of tourism, but is still an emerging market in China. Wine tourism is highly experiential, yet only a few research works have focused on the antecedents and consequences of co-creation experience in the context of wine tourism. In this study, Chateau Changyu Rena Shaanxi, China, was selected as the site of research to explore the impacts of wine tourism experience on co-creation experience, perceived value, and consumer behavior. The Structure Equation Modeling (SEM) method has been used to analyze a sample of 536 respondents who have participated in wine tourism. The results show that most Chinese tourists participated in wine tourism for the first time and spent around 800 Renminbi for wine in average at the winery. In addition, this study is the first to confirm that autonomous of co-creation experience, entertainment, education, escapism, and novelty experience have positive effects on co-creation experience. Education experience, esthetic experience, escapism experience, and hedonism experience are positively correlated with perceived value. Co-creation experience and perceived value are positively correlated with word-of-mouth intention, revisit intention and purchase intention. The results of this study also provide implications for winery operators, guiding them to improve their business strategies, enrich wine tourism experience, encourage tourists to participate in co-creation activities, reward visitors for positive word-of-mouth promotion and offer cost-effective products.